Indikator-Indikator yang Mempengaruhi Tingkat Konservatisme Akuntansi - Intan Puspita Sari; Ceacilia Srimindarti (Owner : Riset dan Jurnal Akuntansi, 2022)
Accounting conservatism is a precautionary principle applied by the company, where revenue is recognized more slowly while expenses are recognized more quickly, so net income will appear lower. The purpose of this research is to examine and analyze the effect of the size of the board of commissioners, leverage, frequency of audit committee meetings, financial distress, and firm size on the level of accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study uses a population of all manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in the last four periods, namely 2017-2020, obtained a population of 677 companies. The sampling method used in this study is a purposive sampling technique with several selected criteria so as to obtain a sample of 369 companies. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale, so it is called secondary data. Data collection techniques using documentation techniques. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the size of the board of commissioners (UDK) and the frequency of audit committee meetings (FPKA) have no effect on the level of accounting conservatism. Meanwhile, financial distress (Distress) and firm size (SIZE) have a significant negative effect on the level of accounting conservatism. Different direction with leverage (DAR) which has a significant effect in a positive direction on the level of accounting conservatism. Keywords: financial distress; frequency of audit committee meetings; conservatism accountancy; leverage; the size of the board of commissioners; company size